SISTEM INFORMASI BANK SAMPAH BERBASIS WEBSITE DI PERUMAHAN KIRANA CIBITUNG RW19 - Amatullah Hidayati Rofi'ah (2023)
The management of services at the Kirana Cibitung RW19 Residential Garbage Bank is still carried out manually, this management is carried out by officers using paper media to record waste bank data. This can cause data loss due to lost paper or human error. This research was conducted with the aim of helping solve problems that occur regarding management that has not been computerized. The flow of this research uses the SLDC (System Development Life Cycle) method with a waterfall approach. This waterfall approach has a clear and structured systems research workflow. At the design stage the author describes the UML (Unified Modeling Language) object-oriented tools with modeling use case diagrams, activity diagrams, sequence diagrams and class diagrams. The development of this information system uses the PHP programming language with the CodeIgniter framework. For testing information systems, the author uses the black box testing method. This research produces a website-based information system that is expected to help waste bank officers in terms of management and service of the Kirana Cibitug RW19 Housing Waste Bank, the possibility of losing customer data, sales results, waste deposit results can be resolved because the data has been properly stored in the database.